Characterization of Lord Cutler Beckett's Antagonist Character, Played by the Main Character, Tom Hollander in Pirates of the Caribbean: The Curse of the Blackpearl: Karakterisasi Karakter Antagonis Lord Cutler Beckett yang diperankan Oleh Tokoh Utama , Tom Hollander dalam Pirates of the Carribean : The Curse of the Blackpearl - Bestari, Errina Candra; Novita, Dian (Indonesian Journal of Education Methods Development, 2023)
The object of the study is Pirates of the Carribean‘s Movie series 1. The data of the study are in the form of explicit sentences and written dialogues . the data of this study are collected by doing the following steps: watching movie carefully for many times, identifying the data related to antagonist character, inventorizing the data, classifying the data, simplifying the data . selecting the data , and at last reporting the data into appendixes . there are several techniques to analyze the data . they are exposing , explaining , interpreting , and the last one is summarizing. the interpretation and the explanation are done from the point of view of sociological approach . The result of this study shows that there are many antagonist conflicts among the characters. the diiferent characters arise cause of individual and selfish societal aspects . Besides, the antagonist character is also found many sectors and has bad effects toward the third social class such as intimidation, physical attack , avoidance between first class toward to third class , and the last extermination. The third class is someone at low caste of social class that always received many kind of humiliation and never get a respect by the highest class of social. Therefore, they give some reactions towards first class who practice antagonist character to the third class such as submission, avoidance, and integration. Finally this study is expected to give more knowledge and understanding about Antagonist character in the real life between the first class among our society.